How 75 years of rubber monocropping affects soil fauna and nematodes as the bioindicators for soil biodiversity quality index. (31st December 2022) - Panklang, Phantip; Thaler, Philippe; Thoumazeau, Alexis; Chiarawipa, Rawee; Sdoodee, Sayan; Brauman, Alain
ABSTRACT: Natural rubber consumption has led to the expansion of rubber ( Hevea brasiliensis ) plantations which affects the deforestation and ecosystem. However, no study of the long-term effect of rubber plantations on soil biodiversity has been carried out yet. This study aimed to assess the long-term impact of continuous rubber monocropping on soil biodiversity, focusing on soil macrofauna and nematode diversity. Three successive rubber rotations at young and old ages were compared with the adjacent forest in Suratthani province, Thailand. Soil biodiversity quality index was calculated from a set of indicators which were combined into a single score to present a functional assessment of the gradient of disturbance. The results showed three negative effects on soil biodiversity (i) the biodiversity quality index immediately declined after deforestation (ii) the old age rubber plantations had a lower soil biodiversity as the nematodes were a main driver of diversity in the young plantation, and (iii) similarly, for the soil chemical properties, the long-term effect of rubber chronosequence evidenced deterioration in the third rotation. Therefore, two rotations of rubber plantation (around 50 years) seemed to be the maximum length of rubber monocropping in terms of soil biodiversity recovery.